2005
DOI: 10.1080/03056240500121230
|View full text |Cite
|
Sign up to set email alerts
|

Role of Interaction between Technological Communities and Industrial Clustering in Innovative Activity: The Case of Hsinchu District, Taiwan

Abstract: Economic development requires knowledge in today's knowledge-based economy. The achievement of economic development in one area depends directly on the efficiency of the attainment, accumulation and application of knowledge and information. These processes rely heavily on the involvement of human resources with technological knowledge and technical skills. Correspondingly, knowledge creation ability and the efficiency of knowledge creation and application determine industrial clustering and economic sustainabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…Previous research has demonstrated that in-house R&D, local academic and research institutes, and foreign companies are the three primary sources of technology for firms in HSIP (Hu et al, 2005b). This work found that R&D cooperation or product design cooperation among firms comprises 30% of all responses ( Table 7), and that R&D cooperation occurs mainly in different hierarchies in related industries in HSIP.…”
Section: Innovative Chains Within Technological Communitiesmentioning
confidence: 79%
“…Previous research has demonstrated that in-house R&D, local academic and research institutes, and foreign companies are the three primary sources of technology for firms in HSIP (Hu et al, 2005b). This work found that R&D cooperation or product design cooperation among firms comprises 30% of all responses ( Table 7), and that R&D cooperation occurs mainly in different hierarchies in related industries in HSIP.…”
Section: Innovative Chains Within Technological Communitiesmentioning
confidence: 79%
“…Beaudry [7] found that industrial clustering influences industry entry, growth, and patenting. Other recent studies address the effects of spatial proximity among firms and show that industrial clustering can lead to innovative activities [8]. Thus, technological capability can be fostered through geographical clustering [9].…”
Section: Bicycle Industry Clusteringmentioning
confidence: 99%
“…In addition, communication efficiency is high, and the cost of communication is lower within the same industrial cluster, making communication more convenient [21,22]. Industrial clustering enables frequent and efficient information exchanges [8], which makes it not merely beneficial to technological innovations but also helpful to formal or informal communications [23,24]. Another benefit of industrial clustering is sharing the cost of infrastructure and resources, which gives an industry cluster the advantage of increased synergies [25,26].…”
Section: Bicycle Industry Clusteringmentioning
confidence: 99%
See 1 more Smart Citation
“…The feedback and reflections suggest that mandating, attracting, and simplifying are useful strategies to promote our VEC model as well as to facilitate social change and create a multiple-win situation for all parties involved. This approach also follows the tao ( ) of the Classic of Changes to provide new knowledge.Keywords: career theory, career counselling, Chinese philosophy, indigenous psychology, career information system, Classic of Changes (Yi Jing) Taiwan has been transforming into a knowledge-based economy (also known as knowledge economy, frequently discussed with issues of informationalism, information revolution, knowledge sharing, knowledge management, intellectual capitalism; Al-Hawamdeh, 2005;Chen & Chiu, 2005;Hu, Lin, & Chang, 2005;Shie & Meer, 2010;So, 2005). The Organization for Economic Cooperation and Development (OECD) defines a knowledge-based economy as 'economies which are directly based on the production, distribution and use of knowledge and information' (OECD, 2005 novating have become common occupational capacities at all levels and in all lines of work.…”
mentioning
confidence: 99%